Інноваційний розвиток опк України на засадах офсетної політики та міжнародного трансферу технологій - Петренко, Л. А.; Трейтяк, М. М.; Petrenko, L. A.; Treitiak, M. M. (Видавництво Львівської політехніки, 2017)
Розглянуто особливості формування офсетної політики в Україні, узагальнено ключові теоретичні положення офсетної політики, проаналізовано світові економічні тренди розвитку ОПК різних країн на засадах офсетної політики та з позиції місця України як країни-реципієнта в офсетних угодах, а також наведено аналіз динаміки процесу формування в Україні законодавчих та організаційних основ офсетної політики у сфері ОПК. Також окреслено основні проблеми та переваги впровадження офсетного законодавства в Україні з позиції інноваційного розвитку ОПК і міжнародного трансферу технологій.

The publication considers the issues regarding the peculiarities of formation of such concepts as "offset" and "offset policy." The article describes the forms and methods of implementing the offset policy in different countries. Besides, the article outlines the basic problems and advantages of the offset policy in Ukraine. The paper discusses the specifics of the formation of the offset policy in Ukraine. The article summarizes the key theoretical principles of the offset policy, analyzes the world economic trends in the development of the defense industry of various countries on the basis of offset policy and from the position of Ukraine as a recipient country in offset transactions, Formation in Ukraine of legislative and organizational bases of offset policy in the sphere of defense industry. Also, the article outlines the main problems and advantages of introducing offset legislation in Ukraine from the point of view of innovative development of the defense industry and international technology transfer. The article emphasizes that the position of the recipient country of technology (potentially Ukraine) in international offset transactions does not have to be passive: it tends to protect its own interests by increasing the involvement of domestic enterprises, transferring technologies to them, using their potential, rather than production capacity of exporter. Thus, for 17 years already Ukraine has been developing and improving the legislative and organizational basis of the offset policy in the sphere of defense industry. However, taking into account the needs of the country, offset programs can ensure the innovative development of the Ukrainian defense industry only if there is an effective national innovation system in the state, an effective scientific and technical policy is defined and implemented, and at the macroeconomic level the chosen models and strategies for innovative development of companies defense industry.
Innovative development of ukrainian militaryindustrial complex on principles of offset policy and international transfer of technologies
Keywords: офсети у сфері ОПК; оборонні офсети; угоди про оборонні офсети; передача технологій; інновації; конкурентоспроможність; military industrial offsets; defense offsets; defense offset agreements; technology transfer; innovations; competitiveness; 339.94; 338.23